Tenure rights and sustainable livelihoods: Implications for land policy - Hofisi, M.; Lukamba, T. M. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
Current development understanding in both policy and academic circles espouses that secure tenure has a significant contribution to poverty alleviation for small-scale farmers. It is under these auspices that the Fast Track Land Reform Programme (FTLRP) was implemented in Zimbabwe. The main aim of this paper was to examine the effect of the tenure system to small scale farmers' livelihoods under the Fast Track Land Reform Programme in Masvingo Province, Zimbabwe. Although literature has been written on land reform, there is a dearth of rigour and political will on pursuing land reform in Southern Africa despite the racially skewed agrarian systems. Key informants who were selected for in-depth interviews are leaders of farmers, government officials, and small scale farmers. The study made use of semi-structured questionnaires as instruments for holding in-depth interviews with key informants. In addition, document review was used to gather secondary data from published literature sourced from the government and other credible publishers. With regards to the livelihoods of small-scale farmers, results indicate that there is potential for the FTLRP to improve their livelihoods. Positive benefits have been noted in a few cases where farmers had their own capital because land was not bankable without legally binding tenure rights. Therefore, farmers face challenges like lack of financial capital, which limits their productive capacity. In addition, farmers reported cases where arbitrary acquisition when political loyalty to the ruling party was suspected. With lack of capital, productivity among small scale farmers was reported to be waning as farmers rely on rain-fed agriculture. Resultantly, value for beef and other small livestock plummeted, thereby affecting the income of farmers. This demonstrates that secure land tenure and poverty alleviation of small-scale farmers are closely linked. By exploring the policy prescriptions of the FTLRP and livelihoods of farmers, this study highlights the salient matters that are critical in land reform policy implementation and research. The main argument of this study is that land reform can positively change thelivelihoods of poor small-scale farmers, provided policy guarantees secure, and bankable title.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Land reform; Livelihoods; Small-scale farmers; Tenure; Land reform; Poverty; Livelihood